UPAYA PEMBERDAYAAN DALAM PENGEMBANGAN KAPASITAS SUMBER DAYA MANUSIA LOKAL UNTUK MENDUKUNG KEBERLANJUTAN PENGELOLAAN DESA WISATA - Lintang Pramundita; Kukuh Miroso Raharjo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the need to strengthen local human resource (HR) capacity to ensure the sustainability of community-based tourism villages. In practice, local communities still face limitations in skills, experience, and access to training. This study was conducted in Pujon Kidul Tourism Village, Malang Regency, East Java, focusing on Café Sawah as its main business unit. The study aims to identify the condition of local HR capacity, the factors influencing the effectiveness of capacity development, and community empowerment efforts to improve HR capacity in tourism village management. A qualitative approach with a case study method was employed. The research subjects included tourism village managers, local workers, and relevant stakeholders. Data were collected through observation, interviews, and documentation and analyzed descriptively. The findings indicate that local HR capacity remains at a developmental stage and has not fully met professional tourism standards, particularly in management, digital promotion, and service innovation. Factors influencing HR capacity development include economic conditions, individual motivation, and competition among tourism destinations. Empowerment efforts have been implemented through community involvement in tourism operations, prioritization of local workers, and the planning of skills training programs; however, these efforts remain insufficiently structured. The study concludes that strengthening local HR capacity requires intensive, sustainable, and needs-based empowerment and training programs to support more effective and sustainable tourism village management.